Aplikasi Kearifan Lokal Wisata Under Water menggunakan User Centered Design berbasis Android - citra Yustitya gobel; Misrawati Aprilyana Puspa (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The southern Bolaang Mongondow district has local wisdom in the field of tourism, especially underwater marine tourism, is. The results of data collection and observation show that the number of diving spots is 54 points with attractive underwater beauty, but based on the identification of the problem, access to information on underwater tourism destinations and activities is still limited, and difficult to access directly because there is no special application for underwater tourism information and information related to diving procedures so that the aim of this research is to design an application for preserving local wisdom for underwater tourism as Android-based digital information to facilitate access to information for underwater tourism enthusiasts who visit diving locations with regular information updates. Research results To achieve the research objectives, namely applying the User Centered Design method with the research results described in the stages of Plan Human Centered Desaign Proses, Understand and Specify the Use Context, Specify of User Requirements, Produce Design of Solutions, dan Evaluate Designs User Requirements which tested using the white box method produces V(G) = E – N + 2 = (5 – 6) + 2 = 1. V(G) = (Predicate Node (P) + 1) = 1 + 0 = 1 and Ciclometic results Complexity (CC) = R1 = 1 and the results of the SUS calculation obtained an average value of 80 which is on the good and excellent scale so that the test results show that the application is designed according to the needs of system users